Rapat sisipan inovatif: Merajut tiga pilar (guru, siswa, orang tua) dalam evaluasi progresif kurikulum merdeka - Bintang, Nayya Hajar (Maliki Interdisciplinary Journal, 2025)
The Merdeka Curriculum requires a more flexible and collaborative evaluation model, but many schools still focus solely on academic assessment. This study aims to describe the implementation of the Merdeka Curriculum evaluation in one of the junior high schools in Malang City, emphasizing a new finding in the form of insert meetings as a reflective evaluation model. A descriptive qualitative approach was used through interviews, observations, and documentation of the deputy principal in charge of curriculum, teachers, and students who participated in the insert meetings in turns. The results showed that insert meetings provided space for students to present their learning achievements, difficulties encountered, and support needs in front of teachers and parents. This evaluation not only assesses academic aspects but also develops character, self-confidence, and strengthens parental involvement in the learning process. Thus, the inter-class meeting becomes an innovation in the Merdeka Curriculum evaluation that is reflective, participatory, and oriented towards strengthening the relationship between schools, students, and families.